Permasalahan Yang Dialami Lansia Dalam Menyesuaikan Diri Terhadap Penguasaan Tugas-Tugas Perkembangannya - Afrizal Afrizal (Islamic Counseling : Jurnal Bimbingan dan Konseling Islam, 2018)
The purpose of this study is to describe and illustrate the problems experienced by the elderly in mastering development tasks. This research is a research field that is qualitative, descriptive. From the results of research can be in the know that, physical strength and health is a major problem that is often faced by the elderly, because the family needs still great while power on the wane so what generated the leter insufficient, retirement is not a lot of problems arise that relate to economic families in meeting the daily needs, the problem of death of spouse is a very heavy problems perceived by the elderly because they often living areas a sense of loneliness and changing roles between them, in forming a relationship with people at not too experienced obstacles, because the elderly usually often follows the recitation or arisan, problems associated with the broader social role is not too experienced a lot of problems, because the elderly are still arriving by the whole community.